Que disent les tapirs ? De la communication avec les non-humains en Amazonie - Cédric Yvinec (Journal de la Société des Américanistes)
What do the tapirs say? About communication with non-human beings in Amazonia. This article compares different communicational events with non-human beings (animals, spirits, dead, etc.) among Lowland Indians from South America. These facts reveal to be the matter for the same general interpretation ; they use the same language based on kinship.